The Effect of Work Communication, Motivation and Job Training on Employee Productivity at PT Sushi Indo Sukses Mandiri Medan - Ina Namora Putri Siregar; Elta Romauli Sijabat; Listra M Siburian; Nabila Anjani Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The influence of work communication, motivation, and job training are valuable aspects that need to be considered for every company organization to support overall employee performance improvement. Therefore, this study intends to understand the effect of work communication, motivation, and job training on employee performance at PT. Sushi Indo Sukses Mandiri Medan either partially or simultaneously. The research method uses quantitative descriptive analysis. The population in this study were all employees at PT. Sushi Indo Sukses Mandiri Medan, totaling 74 individuals. The data analysis method used the F-Test, T-Test, and Multiple Linear Regression, while the data analysis used SPSS version 20. Based on the results of data analysis in this study, partially it can be seen that work communication (X1) has a value of 1. t_count mark t_table is 1.6657 then the number t_count > t_table of (1.944>1.6657) and the number of sig 0.056>0.05 Regarding this, it means that the accepted hypothesis is that work communication according to partial has a good and significant impact on the achievement of employees at PT. Sushi Indo Sukses Mandiri Medan. The results of the study show that the motivation variable (X2) has 4.801 and is worth 1.6657, so the total value of t_count t_table t_count>t_table (4.801 >1.6657) and the number of sig 0.000 <0.05. This means that the hypothesis is accepted, namely work motivation according to partial which has a positive and significant impact on the achievement of workers. The results of the study prove that the job training variable (X3) has a value of 3.411 and a value of 1.6657 then t_count t_table t_count > t_table (3.411 >1.6657) then the sig value is 0.001<0.05. This means that the hypothesis of receiving job training partially has a good and significant impact on the achievement of employees at PT Sushi Indo Sukses Mandiri Medan.